2017
DOI: 10.18203/2320-1770.ijrcog20175240
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors affecting the trends of permanent sterilization: a decadal analysis in a tertiary care institute

Abstract: Background: Permanent sterilization is a preferred method of contraception worldwide. In spite of popularization of temporary methods, it is used by 2/3rd of married women using any contraception. It has a low incidence of complications and failure rate and is cost-effective. Various socio-demographic factors play a role in acceptability of this method. It has an important role in controlling the total fertility rate.Methods: A retrospective record based analysis was done in armed forces personnel undergoing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
0
4
1
Order By: Relevance
“…The findings also partly agree with those of a study in Nigeria on female surgical sterilization which found that more than half of the women who opted for sterilization were aged between 35 to 39 years [ 23 ]. However, the study disagrees with findings of a study done in India where sterilization method uptake and acceptance was at a much younger age (mean age 28.9 years) among women [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The findings also partly agree with those of a study in Nigeria on female surgical sterilization which found that more than half of the women who opted for sterilization were aged between 35 to 39 years [ 23 ]. However, the study disagrees with findings of a study done in India where sterilization method uptake and acceptance was at a much younger age (mean age 28.9 years) among women [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…17 Bharadwaj et al, depicted highest (more than 80%) acceptance in couples with two children in their decadal analysis of trends of permanent sterilization. 18 But their study was facility based, and the population visiting a health institute may have differential characteristics and may not represent the community; this may explain the difference with present study.…”
Section: Discussionmentioning
confidence: 64%
“…Religion of the couples was not found to affect the decision of accepting permanent methods of contraception, but in other studies acceptance of contraception was found to be significantly less among the Muslims. 14,18,19 Non-acceptors were significantly higher among the couples living in joint families. This suggests the influence of family in decision making among couples.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations